Managing fatigue in team sports: a brief review of concurrent training effects within the microcycle - Grammenou, M.; Nulty, C. D. (Strength and Conditioning Journal, 2025)
Concurrent training (CT), which combines resistance exercise and energy systems conditioning, is the default approach to preparation in high-intensity intermittent ("stop and go") team sports. This review provides an overview of CT, emphasizing its complexities and challenges in managing fatigue and optimizing performance. These complexities are specifically compounded by the variability in game demands across the season, where the presence of intensified and nonintensified competition periods necessitates a flexible and adaptive training approach. In this context, there are essential training variables to consider, including intensity, volume, session order, and recovery intervals between sessions. In addition, nontraining variables such as travel, sleep, and nutrition play a role in the fatigue experienced while training and competing. These variables interact to influence acute performance and training adaptations and can be strategically adjusted by strength and conditioning practitioners. The aim of this review is to provide a comprehensive understanding of fatigue management for practitioners in team sports, emphasizing the complexities and challenges of CT and offering simplified practical recommendations for adjusting training variables within any given microcycle.